The excellent performance and mechanism of activated carbon air cathode doped with different type of cobalt for microbial fuel cells. (15th July 2016) - Liu, Ziqi; Ge, Baochao; Li, Kexun; Zhang, Xi; Huang, Kan
Highlights: Two type of cobalt modified AC catalysts were successfully used in air-cathode MFCs. The maximum power density of Co/AC was 1420.8 ± 54 mW m −2, 63.8% higher than control. Co3 O4 /AC responded highest i 0 which was 2.6 times higher than the control. Co3 O4 nanosheet formed on the AC with the surface area increased and the R ct reduced. The high crystallization resulted in the significant catalytic activity of Co3 O4 . Abstract: A novel cobalt decorated activated carbon (AC) air cathode with facilitated oxygen reduction activity is developed for microbial fuel cells (MFCs). Two kinds of cobalt modified cathodes Co(OH)2 /AC and Co3 O4 /AC were prepared via a simple electrodeposition. The electrodeposition process was optimized to achieve high a surface area and pore volume structure. Transmission electron spectroscopy (TEM) analyses confirmed that Co3 O4 and Co(OH)2 nanosheets were homogeneously distributed on the AC. Compared to raw AC. Electrochemical evaluation showed that the onset potentials towards oxygen reduction reaction (ORR) of Co(OH)2 /AC and Co3 O4 /AC shifted to higher potential and the exchange current densities were increased by 2.6 times and 1.6 times, respectively. The MFCs with Co3 O4 /AC reached a maximum power density of 1420.8 ± 54 mW m −2, significantly improved performance by 64% in relative raw AC.